2013
DOI: 10.3389/fendo.2013.00135
|View full text |Cite
|
Sign up to set email alerts
|

Exocytosis and Endocytosis in Neuroendocrine Cells: Inseparable Membranes!

Abstract: Although much has been learned concerning the mechanisms of secretory vesicle formation and fusion at donor and acceptor membrane compartments, relatively little attention has been paid toward understanding how cells maintain a homeostatic membrane balance through vesicular trafficking. In neurons and neuroendocrine cells, release of neurotransmitters, neuropeptides, and hormones occurs through calcium-regulated exocytosis at the plasma membrane. To allow recycling of secretory vesicle components and to preser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 56 publications
(64 reference statements)
2
18
0
Order By: Relevance
“…Thus, we employed adrenal chromaffin cells, a well-established model to study calcium-regulated exocytosis, given that these cells use similar molecular machinery as neurons 33,34 . After LDCVs fuse with the plasma membrane in chromaffin cells, an orchestrated process of compensatory endocytosis efficiently removes the added membrane and proteins, and delivers them to a near-Golgi area, a process that takes tens of minutes 35 . We found that chromaffin cells, like neurons, contain mRNAs for all three endophilins.…”
mentioning
confidence: 99%
“…Thus, we employed adrenal chromaffin cells, a well-established model to study calcium-regulated exocytosis, given that these cells use similar molecular machinery as neurons 33,34 . After LDCVs fuse with the plasma membrane in chromaffin cells, an orchestrated process of compensatory endocytosis efficiently removes the added membrane and proteins, and delivers them to a near-Golgi area, a process that takes tens of minutes 35 . We found that chromaffin cells, like neurons, contain mRNAs for all three endophilins.…”
mentioning
confidence: 99%
“…Hence, exo‐endocytosis coupling leads then to recycling of post‐exocytotic internalized granule membrane back to the Golgi apparatus, starting a new life for the secretory granule (Houy et al . ). Recently lipids generated upon exocytosis have been proposed to contribute to the exo‐endocytosis coupling (Yuan et al .…”
Section: Lipids and Exocytosis Of Secretory Granulesmentioning
confidence: 97%
“…Molecular mechanisms underlying the preservation of granule mem- brane identity after fusion with plasma membrane remains unclear, but it has been proposed that specific lipid microdomains might contribute to prevent diffusion of granular components. Hence, exo-endocytosis coupling leads then to recycling of post-exocytotic internalized granule membrane back to the Golgi apparatus, starting a new life for the secretory granule (Houy et al 2013). Recently lipids generated upon exocytosis have been proposed to contribute to the exo-endocytosis coupling (Yuan et al 2015).…”
Section: Lipids Regulating Molecular Mechanisms Of Priming Stepsmentioning
confidence: 99%
“…2) may have some relevance as endocytosis is a fundamental process of membrane recovery in neurons upon calcium-related exocytosis of secretory vesicles (Houy et al, 2013). Intracellular sequestration of ECs, which would provide an intracellular compartment that is not free to equilibrate with the extracellular AEA pool, was suggested .…”
Section: Model Of Endocytosis-mediated Aea Uptake and Intracellularmentioning
confidence: 99%